'Glorious Auxiliaries'? Gender, Participation, and Subordination in the Chartist Movement (1838–1851). Issue 1 (April 2020) - Morne, Emmanuelle
Abstract : In his famous poem 'Woman's Mission', published in 1856, Chartist leader William Lovett extolled the moral virtues of women not only for the care of their families but also for society in general. At the heart of Lovett's political strategy was an ambitious educational programme designed to promote the moral and intellectual improvement of the working class mainly though the influence of women. Women therefore were originally supposed to play a central part in the Chartist scheme for a new society. However, the chief obstacle to the accomplishment of women's mission within the movement lay in their confinement to a domestic and maternal role as well as in the established hierarchy between the sexes and men's dominant position within society and the public sphere. The relationships between male and female Chartists were necessarily affected by these constraints, but nevertheless allowed for considerable ambivalence and ambiguity. Historian David Jones asserted in the early 1980s, 'Historians have underestimated the degree of female participation in the Chartist movement'. Despite the existence of more recent studies on the subject, the question of the balance of power between men and women involved in the movement remains an under-researched area. Relying essentially on primary sources, this article intends to address the issue of women's contribution to the Chartist movement from 1838 to 1848 through the concepts of gender, participation, and subordination, taking into account both the masculine and feminine perceptions of women's involvement in Chartism.